Odpowiedź :
a)
w(p)=1, w(q)=1
q=>p [^4 =2]=>[(-2)2=4] w(q=>p)=1
q<=>p [^4 =2]<=>[(-2)2=4] w(q<=>p)=1
b)
w(p)=0, w(q)=0
q=>p [9 *0,25 >/ 11*0,25 ]=>[9>/11] w(q=>p)=1
q<=>p [9 *0,25 >/ 11*0,25 ]<=>[9>/11] w(q<=>p)=1
w(p)=1, w(q)=1
q=>p [^4 =2]=>[(-2)2=4] w(q=>p)=1
q<=>p [^4 =2]<=>[(-2)2=4] w(q<=>p)=1
b)
w(p)=0, w(q)=0
q=>p [9 *0,25 >/ 11*0,25 ]=>[9>/11] w(q=>p)=1
q<=>p [9 *0,25 >/ 11*0,25 ]<=>[9>/11] w(q<=>p)=1
a) p: (-2)2=4 q:^4 =2 tutaj zawartość p =1 ,a q=1
q=>p ===> 1=>1 prawda
q<=>p ==> 1<==>1 prawda
b)p:9>/11 q: 9 *0,25 >/ 11*0,25 p=0 q=0
q=>p ===> 0=>0 prawda
q<=>p ==> 0<==>0 prawda
q=>p ===> 1=>1 prawda
q<=>p ==> 1<==>1 prawda
b)p:9>/11 q: 9 *0,25 >/ 11*0,25 p=0 q=0
q=>p ===> 0=>0 prawda
q<=>p ==> 0<==>0 prawda